2023
DOI: 10.3390/ijms24108816
|View full text |Cite
|
Sign up to set email alerts
|

Natural Variation Confers ‘Aiyuan 38’ Citrus Mutant a New Color and Unique Flavor

Abstract: Citrus exhibits unique nutritional values. Most citrus cultivars are derived from mutations. However, the effect of these mutations on fruit quality is unclear. We have previously found a yellowish bud mutant in the citrus cultivar ‘Aiyuan 38’. Therefore, this study aimed to determine the effect of the mutation on fruit quality. ‘Aiyuan 38’ (WT) and a bud mutant variant (MT) were used to analyze variations in fruit color variation and flavor substances using colorimetric instruments, high-performance liquid ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…To comprehensively investigate the volatile changes between WT and MT, different developing fruits were subjected to aroma profile analysis. Although MT was clearly distinguished from the orange-colored WT at ripening stages by its yellowish flavedo ( Wang T. et al., 2023 ), there was no visible difference in pulp color between the two varieties during fruit development ( Figure 1A ). HS-SPME-GC-MS was adopted to evaluate the differences in volatiles composition and content of pulps between WT and MT.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To comprehensively investigate the volatile changes between WT and MT, different developing fruits were subjected to aroma profile analysis. Although MT was clearly distinguished from the orange-colored WT at ripening stages by its yellowish flavedo ( Wang T. et al., 2023 ), there was no visible difference in pulp color between the two varieties during fruit development ( Figure 1A ). HS-SPME-GC-MS was adopted to evaluate the differences in volatiles composition and content of pulps between WT and MT.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study has identified a yellow mutant of ‘Ehime 38’ ( Citrus reticulata ) with a richer aroma in pulps relative to the wild type ( Wang T. et al., 2023 ). However, the accumulation patterns of volatile compounds during fruit development in both varieties and molecular mechanism remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…The organic acid components (fresh weight) of the pulp were detected by high performance liquid chromatography (LC-1260; Agilent Technologies, Sacramento, CA, USA). Detection of the content of organic acids followed the method described by Wang et al [ 43 ] with slight modifications. The pulp samples were weighed to 0.5 g, ground with pre-chilled 3 mL of 0.2% metaphosphoric acid, fixed to 6 mL, and centrifuged at 4 °C for 15 min at 12,000 r min −1 .…”
Section: Methodsmentioning
confidence: 99%
“…Fruit weight was measured by electronic scales and vertical/transverse diameter was measured by vernier calipers. Total soluble solids (TSS) and titratable acids (TA) were measured using a glycolic acid meter (Pocket PAL-BXIACID1; ATAGO, Tokyo, Japan) [54]. V C was measured according to the method described by previous authors [55].…”
Section: Standard Quality Parametersmentioning
confidence: 99%
“…Headspace solid-phase microextraction-gas chromatography-mass spectrometry (HS-SPME-GC-MS) was used to extract and detect VOCs in different parts of fruits. Fruit tissues (0.1 g peel and 0.5 g pulp) were ground to a powder using liquid nitrogen and quickly placed in a headspace flask, then 5 mL of saturated sodium chloride solution and 50 µL of 1-hexanol (0.1%, v/v) were added and VOCs were measured after equilibration and extraction [54]. The inlet temperature, desorption time and column chamber warming procedures were performed as previously described [60].…”
Section: Pulp and Peel Volatile Organic Compounds (Vocs) Identificati...mentioning
confidence: 99%